Facebook dalam Kajian Kualitatif: Menjawab Pertanyaan 'Apa' dan 'Bagaimana' - Jamil, Nurul Akma; Khuan, Lee; Ai Theng, Cheong; Muda, Siti Mariam (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2024)
The rapid development and widespread use of internet-based technology have changed the research landscape. In line with these developments, Facebook has become a new avenue in research. This paper discusses, firstly, how Facebook can be utilized and, secondly, the complexities and practicalities of using this platform when conducting qualitative research. Utilizing Facebook in qualitative research is challenging due to the vast amount of data it contains and the ethical issues involved. However, understanding the features of Facebook and the involvement of gatekeepers may facilitate the research process. Facebook has become a viable tool in qualitative research for collecting data and recruiting participants. However, a strategy is required to facilitate the research process. Using Facebook in research can be a powerful tool but researchers should use it with caution and thoroughly evaluate the implications for practice before doing so.